The analysis on creep failure mechanism of nickel-based single crystal superalloys deposited with different molten salts. (May 2023) - Liu, H.; Wang, X.M.; Zhao, Z.N.; Li, H.T.; Yang, W.Z.; Li, L.
Highlights: The failure mechanism of DD6 under the effect of the Na2 SO4 and the mixed salts of Na2 SO4 and NaCl are fully studied. The basic factor for the declination of effective cross-section is studied based on microstructural characteristics. The driving factor of micro-crack propagation under the influence of hot corrosion is discussed. The rupture of nickel-based single crystal superalloys deposited with different salts is determined by its corrosive behaviors. Abstract: The creep properties of nickel-based single crystal superalloys under the effect of the Na2 SO4 salt and the mixed salts of Na2 SO4 and NaCl (75 % Na2 SO4  + 25 % NaCl) are investigated in this paper, respectively. The failure mechanism influenced by the γ/γ′ phase evolution and element dissolution is fully discussed through the elemental distribution analysis and the fractographic analysis by Scanning Electron Microscope (SEM) with energy-dispersive spectrometer (EDS). The results show that the existence of NaCl and Na2 SO4 result in the appearance of the tearing ridge and the cleavage-like plane, respectively. Thus, the failure of the specimen deposited with Na2 SO4 is mainly the cleavage-like fracture, and that of the specimen deposited with mixed salts presents a mixed mode of cleavage-like plane and tearing ridge. According to the EDS analysis, the failure mechanisms of nickel-based single crystal superalloys deposited with different molten salts are determined by its corrosive behaviors. The Na2 SO4 is overrun by the sulfidation and oxidation reactions on surface of specimen due to its lower diffusion rate, so the sulphidation attack almost appears on surface and the further permeation is hardly observed. While the existence of NaCl in mixed salts leads to the generation of volatile metal chlorides, which directly promotes the substrate to be exposed in corrosive environment. Therefore, the declination of effective cross-section is the only reason for the fracture of nickel-based single crystal superalloys deposited with Na2 SO4, and the mixed mode is presented on the fracture of the specimens deposited with mixed salts.